Multi-wavelength mode-locked erbium-doped fiber laser with photonic crystal fiber in figure-of-eight cavity - Tiu, Z.C.; Zarei, A.; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2016)
A simple passively multi-wavelength mode-locked EDFL is proposed and demonstrated based on figure-of-eight set up. A 50 m long PCF and 20 km long SMF are incorporated in the cavity as birefringent fiber. The EDFL generates a stable multi-wavelength laser with spacing of 0.47 nm and mode-locked pulse at threshold pump power of 137.0 mW. By varying the pump power from threshold power to maximum 146 mW, pulse repetition rates and pulse width remain as 185 kHz and 1.87 μs respectively. The maximum pulse energy of 2 nJ is obtained at pump power of 146.0 mW.